Racial and Ethnic Identities in the Media - Arapoglou, Eleftheria; Kalogeras, Yiorgos; Nyman, Jopi (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
XVII, 287 p. 5 illus., 3 illus. in color.